Now You See It, Now You Don't: The Disappearing Collection of Western University's D.B Weldon Library - Mullender, Alec; James, Marnie (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
The mass culling of libraries' print collections has often been questioned by librarians and library users, yet it has become more common in recent decades. Despite several high-profile controversies, the removal and subsequent disposal of large portions of physical collections are still seen by many library authorities as an effective way to create space and pave the way for innovation. Guided by a progressive series of photographs, this article examines the large-scale removal of books from Western University’s D.B Weldon Library as part of a renovation project in 2019. It also looks at the direct impact of these actions on a contemporary library research project that was undertaken by the authors. Focusing specifically on the E, HQ, and HV Library of Congress call number ranges, the changes to the stacks are shown in real time as materials are removed from the collection to be discarded or placed in storage. The authors raise questions about the functions and uses of libraries in our current neoliberal era as well as the logic of an academic library prioritizing study spaces and communal areas at the expense of a well-respected physical collection.